Deaf children's non-verbal working memory is impacted by their language experience - Marshall, Chloë; Jones, Anna; Denmark, Tanya; Mason, Kathryn; Atkinson, Joanna; Botting, Nicola; Morgan, Gary (Frontiers in Psychology, 2015)
Recent studies suggest that deaf children perform more poorly on working memory tasks compared to hearing children, but do not say whether this poorer performance arises directly from deafness itself or from deaf children’s reduced language exposure. The issue remains unresolved because findings come from (1) tasks that are verbal as opposed to non-verbal, and (2) involve deaf children who use spoken communication and therefore may have experienced impoverished input and delayed language acquisition. This is in contrast to deaf children who have been exposed to a sign language since birth from Deaf parents (and who therefore have native language-learning opportunities). A more direct test of how the type and quality of language exposure impacts working memory is to use measures of non-verbal working memory (NVWM) and to compare hearing children with two groups of deaf signing children: those who have had native exposure to a sign language, and those who have experienced delayed acquisition compared to their native-signing peers. In this study we investigated the relationship between NVWM and language in three groups aged 6-11 years: hearing children (n=27), deaf native users of British Sign Language (BSL; n=7), and deaf children non native signers (n=19). We administered a battery of non-verbal reasoning, NVWM, and language tasks. We examined whether the groups differed on NVWM scores, and if language tasks predicted scores on NVWM tasks. For the two NVWM tasks, the non-native signers performed less accurately than the native signer and hearing groups (who did not differ from one another). Multiple regression analysis revealed that the vocabulary measure predicted scores on NVWM tasks. Our results suggest that whatever the language modality – spoken or signed – rich language experience from birth, and the good language skills that result from this early age of aacquisition, play a critical role in the development of NVWM and in performance on NVWM tasks.